Mechanical behavior of cellular networks of fiber bundles stabilized by adhesion. (1st May 2020) - Negi, V.; Picu, R.C.
Abstract: In this work, we study the mechanical behavior of non-crosslinked networks of fibers that interact adhesively. Adhesion drives fiber organization into bundles and a network of fiber bundles forms as a result of this process. Bundles split and re-connect forming specific triangular features at all bundle intersections, with role in network stabilization. The structure of such networks has been discussed in the literature, but their mechanics remains largely unexplored. We show here that such networks are exceptionally stable, and despite the absence of crosslinks between fibers behave, at relatively small strains, essentially similar to crosslinked networks, in which the role of crosslinks is played by the triangular structures at bundle intersections. We also provide new results regarding the effect of the network architecture on the type of strain stiffening observed in tension. The results apply to carbon nanotube structures, such as buckypaper, and various connective biological tissue in which collagen fibrils form bundles and the tissue is a network of collagen fibril bundles.